Advanced control system design - Bernard Frieldland (Prentice-Hall, 1996)
The book describes how the methods of modern control theory can be systematically applied to practical design problems, emphasizing the development of intuition through examples rather than mathematical technicalities. Examples of such topics are the following: How to deal with parasitic phenomena, such as friction on backlash; how to combine data from discrete-time and continuous-time sensors; how to use zero-crossing and other highly quantized observation data in designing the state observer; how the extended separation principle effectively deals with the "integratorwindup"; how to deal with saturation